Tito, the Bloc-Free movement, and the Prague Spring - Jakovina, Tvrtko (2010)
Based on the documents in the Archive of Yugoslavia and former Archive of the Preseident of the Republic (Tito's Archive) in Belgrade, Serbia, British and American documents and published sources, article gives genesis of the Yugoslav policy vis-a-vis the Prague Spring and the Warsaw Pact intervention in Czechoslovakia in August 1968.
Projekt MZOS
ENG